Dependence of the Elastic Stiffness Tensors of PETN, α‐RDX, γ‐RDX, ϵ‐RDX, ϵ‐CL‐20, DAAF, FOX‐7, and β‐HMX on Hydrostatic Compression. Issue 4 (18th February 2022) - Cawkwell, Marc J.; Zecevic, Milovan; Luscher, D. J.; Ramos, Kyle J.
Abstract: The dependence of the components of the elastic stiffness tensors (or elastic constants) of the organic explosives PETN, RDX, CL‐20, DAAF, FOX‐7, and HMX on hydrostatic pressure up to 10 GPa have been computed using dispersion‐corrected density functional theory. We report the evolution of lattice parameters and the non‐zero stiffnesses for the tetragonal, orthorhombic, and monoclinic crystal symmetries. Linear and quadratic dependencies of the components of the elastic stiffness tensors on volumetric compression and hydrostatic pressure are tabulated for use in single crystal plasticity models. Abstract :